2006
DOI: 10.3892/ijmm.17.5.721
|View full text |Cite
|
Sign up to set email alerts
|

Efficient differentiation into skin cells of bone marrow cells recovered in a pellet after density gradient fractionation

Abstract: Abstract. We had previously demonstrated the participation of whole bone marrow cells from adult mice in the reconstitution of skin, including the epidermis and hair follicles. To get an insight into cell populations that give rise to the epithelial components of the reconstituted skin, we fractionated bone marrow cells derived from green fluorescent proteintransgenic mice by density gradient. Unexpectedly, we found that a substantial amount of mononucleated cells (~30%) was recovered in the pellet fraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Our results suggest that UC-MSCs engrafted in the wound release proangiogenic factors, subsequently leading to MSC-mediated enhanced angiogenesis. Differentiation of MSCs into keratinocytes found in our study was consistent with the findings of similar other studies [51, 52]. In our study, we found that injection of CM could accelerate wound closure, and the enhancement was even better and more rapid than that achieved by UC-MSC transplantation in contrast to the results obtained by Wu et al [18], although they used MSC from a different source.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that UC-MSCs engrafted in the wound release proangiogenic factors, subsequently leading to MSC-mediated enhanced angiogenesis. Differentiation of MSCs into keratinocytes found in our study was consistent with the findings of similar other studies [51, 52]. In our study, we found that injection of CM could accelerate wound closure, and the enhancement was even better and more rapid than that achieved by UC-MSC transplantation in contrast to the results obtained by Wu et al [18], although they used MSC from a different source.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we observed a distinct CD45- cell population within the rat bone marrow cells which clearly did not belong to the erythroid line (Figure 2D). In total the CD45- population was almost completely depleted after Ficoll DGC (15% recovery of total CD45- cells in lysed bone marrow), a finding that is supported by Medina et al [38] who found many non-erythroid CD45- cells within the usually discarded pellet after DGC. By contrast, in our rat study, both Percoll and MACS separation conserved a large proportion of this population (41% and 57% of lysed bone marrow; Figure 4A).…”
Section: Discussionsupporting
confidence: 56%
“…By contrast, in our rat study, both Percoll and MACS separation conserved a large proportion of this population (41% and 57% of lysed bone marrow; Figure 4A). Interestingly, these CD45- cells seem to contain specific stem cell populations such as MSCs, VSEL, epithelial progenitors [38], multilineage inducible cells [39] and endothelial progenitor cells [40] and might thus be relevant for therapeutic effects of BMNCs. In line with these observations, it was recently described that most of the bone marrow MSCs were discarded during Ficoll DGC due to their aggregate nature [23], and that whole bone marrow, but not BMNCs obtained by Ficoll DGC improved functional recovery after experimental myocardial infarction [41].…”
Section: Discussionmentioning
confidence: 99%
“…This was until the trans-differentiation ability of AMMs into cardiomyocytes and keratinocytes was reported [7], [42], [43]. Additionally, attempts to implant allogeneic fibroblastshas resulted in low engraftment rates in wounds and caused increased inflammation [44], [45].…”
Section: Discussionmentioning
confidence: 99%